ANALISIS SISTEM PENATAAN DAN LASHING MUATAN DI KAPAL RO-RO SEBAGAI UPAYA DALAM MENINGKATKAN KESELAMATAN PELAYARAN - Galih Sakti Cahyo Samudro Armando Agustiawan; Kuncowati Kuncowati; Supangat Supangat (Departemen Teknik Kelautan Universitas Hasanuddin, 2026)
Cargo arrangement and lashing systems on Ro-Ro vessels play an important role in maintaining ship stability and navigation safety. This study aims to evaluate the effectiveness of cargo arrangement and securing practices on a RoRo vessel and to identify the factors affecting their performance. The research employed a quantitative descriptive method through direct observation, literature review, and questionnaires distributed to 10 crew members of KM Mutiara Ferindo 5. The results show that 70% of the crew had not received formal training, 40% considered the lashing process not yet in accordance with standards, and 50% stated that full lashing was only carried out during bad weather conditions. The main problems identified include the absence of written standard operating procedures, worn lashing equipment, and inconsistent supervision. This study recommends the preparation of standard operating procedures and a Cargo Securing Manual, regular technical training, and periodic inspection and renewal of lashing equipment to improve navigation safety and reduce the risk of cargo shifting.